Implementation of medical research module and the effect to medical students’ knowledge and perceptions - Agustina Arundina Triharja Tejoyuwono; Ita Armyanti (International Journal of Evaluation and Research in Education (IJERE), 2022)
Research activity is one of the requirements for medical students in order to finish their study. Therefore, it needs to examine the knowledge and perceptions of medical students about medical research. The research design was an experimental one-group pretest-posttest design, involving 86 medical students, with the statistical tests using the Wilcoxon Signed-Rank Test. After the module implementation, the students’ knowledge about research had improved in the concept of theoretical basis, the concept of research methodology, and the biostatistics methods. However, there was no improvement in bioethical knowledge. Close relations between the result of pre- and post-research modules implementation were shown in the knowledge about theoretical basis, about research methodology, and the perception of workloads in college have (p<α). There were significant changes in knowledge (Z=-2.867, p=0.004) and perceptions (Z=-1.964, p=0.050) of the medical students pre- and post-research module. Giving research modules early, along with social and academic support for medical students, would improve their knowledge and positive perceptions towards research.